Practice nurses and antismoking education. Issue 6517 (8th February 1986) - Sanders, D J; Stone, V; Fowler, G; Marzillier, J
Abstract : A questionnaire on antismoking activities and education was sent to 369 nurses in general practice. The response rate was 80%. Although most of the nurses sometimes advised patients about smoking, routine antismoking education occurred less frequently. Only a few regularly referred smokers to other agencies for help, recommended aids to stop smoking, or used antismoking literature. Although the nurses thought that they had an important role in helping smokers to give up, they expressed little confidence in their effectiveness, believing that advice from the general practitioner and the smoker's personal determination to give up have more impact. The nurses expressed a need for training in antismoking education. Seventy seven per cent were interested in attending seminars and listed information about smoking, techniques for stopping, and counselling skills as priorities. If practice nurses are to use opportunities in primary care to help smokers there is clearly a need to provide further training and to establish the effectiveness of nurses in their role as smoking educators.